The role of fatherhood towards early childhood in Javanese culture: Ethnoparenting study in Wonolelo - Mashar, Riana; Sofyan, Iyan; Ansori, Irfan; Rahmah, Fatimah; Huzaimah, Siti; Gunawan, Marina Tri N (Universitas Ahmad Dahlan, 2024)
The aim of this research is to explore the role of fathers in caring for early childhood children in Javanese culture. The phenomenon of fatherlessness in parenting is increasingly widespread in Indonesia. The Javanese tribe, one of the largest ethnic groups in Indonesia, was the sample in this research. The research method used is qualitative research with an ethnoparenting approach. The research locus was determined based on the subject's domicile, which was the Wonolelo area, Pleret, Bantul, Yogyakarta. The snowball technique was used as a method in selecting respondents. Involving 14 families as participants, the data was collecting through direct observation and interviews. Data were analyzed using thematic analysis. The research results show that the role of the father in the Javanese tribe of Wonolelo Village is still the same as the role of most fathers in Indonesia, namely as a decision maker and as a leader, the economic provider, where the family still adheres to a patriarchal culture. Fathers do not always directly involve in parenting at children's daily life. Fathers play more of a role as disciplinarians, role models in carrying out religious teachings, cultural and social traditions. The mother dominates the parenting role at home. It is essential for fathers to increase their parenting role by interacting directly to meet children's psychological and physiological needs.